Location of FACTS Devices in Power Systems: Application to the IEEE 9 bus System (2019)
This paper proposes a methodology to find the location of a flexible transmission system in AC in a power system, based on a nodal order and the analysis of repetitive power flows. To check the proposed methodology, the IEEE 9 bus system was taken as a case study. Results obtained were analyzed in two moments, initially the power flow is simulated without modifications, reading of the loss variables in the transmission lines, power factor, active and reactive power and voltage in p.u. in the buses. Then the power flow is simulated again and the resulting values are taken and compared with those initially taken, finding that by locating the device in bus 5, a better response is obtained. © 2019 IEEE.